2022
DOI: 10.33687/jsas.010.02.4059
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Harassment—a Comparative Study of India & Pakistan in the light of Recent Developments in Pakistan

Abstract: The study is a comparison and analysis of the laws relating to sexual harassment in Pakistan and India, in light of the legal feminist theory. An attempt is made to identify gaps in them and amendments are proposed. The law is supposed to act as a protector, but it seems to have failed in providing much-needed protection to women. The study discusses the reasons behind this failure and proposes certain amendments for lawmakers to ensure women’s rights in the current changing environment. The study is an attemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…It has been found that income and income square has a positive and significant relationship with the household’s savings in Pakistan; indicating that the household’s savings tend to increase with income. Various earlier studies (including Agrawal et al, 2009, Ahmad & Asghar, 2004, Rehman et al, 2011) also come to a similar conclusion.…”
Section: Conclusion and Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…It has been found that income and income square has a positive and significant relationship with the household’s savings in Pakistan; indicating that the household’s savings tend to increase with income. Various earlier studies (including Agrawal et al, 2009, Ahmad & Asghar, 2004, Rehman et al, 2011) also come to a similar conclusion.…”
Section: Conclusion and Discussionsupporting
confidence: 70%
“…Rehman et al (2010, 2011) find that in Multan (a city in Pakistan), female labour participation, household income, dependency rate and size of land ownership have a positive impact on savings. However, family size, education of household head and value of house hurt savings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The revocation of the MFN status is just one manifestation of the broader Hindutva-driven policies that shape India's stance on Kashmir and its relations with Pakistan. 25 To de-escalate tensions and promote dialogue, it is imperative to address the underlying Hindutva element in India's policies. Confidencebuilding measures, inclusive approaches, and meaningful engagement are necessary to bridge the trust deficit and work towards a peaceful resolution of the Kashmir dispute.…”
Section: India's Revocation Of Mfn Status For Pakistanmentioning
confidence: 99%